2023
DOI: 10.1007/s00439-023-02563-z
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the mitochondrial ribosomal subunit, MRPL50, causes autosomal recessive syndromic premature ovarian insufficiency

Abstract: Premature ovarian insufficiency (POI) is a common cause of infertility in women, characterised by amenorrhea and elevated FSH under the age of 40 years. In some cases, POI is syndromic in association with other features such as sensorineural hearing loss in Perrault syndrome. POI is a heterogeneous disease with over 80 causative genes known so far; however, these explain only a minority of cases. Using whole-exome sequencing (WES), we identified a MRPL50 homozygous missense variant (c.335T > A; p.Val112Asp)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…To gain insights into the mechanisms responsible for the increased specific activities, we assessed the relative complex abundance (RCA) 25 by grouping mitochondrial proteins quantified by proteomics in the liver of NCD-fed LMKO mice according to the macromolecular complexes to which they belong (Fig. 2H , Supplementary Dataset 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…To gain insights into the mechanisms responsible for the increased specific activities, we assessed the relative complex abundance (RCA) 25 by grouping mitochondrial proteins quantified by proteomics in the liver of NCD-fed LMKO mice according to the macromolecular complexes to which they belong (Fig. 2H , Supplementary Dataset 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, mutations in mitoribosomal proteins lead to variable disease phenotypes ( Table S1 ). 16 , 21 , 22 , 23 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 To date, snMRP proteins associated with human disease are mS22, mS23, mS25, mS34, and mS39. 22 , 32 , 36 , 37 , 39 All reported patients have mitoribosome instability.…”
Section: Discussionmentioning
confidence: 99%
“…Miao C et al (46) found that granulosa cell insufficiency in POI was associated with elevated ROS levels and reduced mitochondrial membrane potential (MMP) and adenosine triphosphate(ATP), suggesting considerable mitochondrial dysfunction. Moreover, Bakhshalizadeh S et al found that mitochondrial ribosomal protein L50 (MRPL50) error variants destabilize mitochondrial ribosomes, leading to oxidative phosphorylation deficiency and syndrome POI (47), highlighting the importance of mitochondrial support in ovarian development and function. Mitochondria are extremely abundant in the oocyte, not only providing energy but also acting as signal transduction hubs to regulate physiological activities such as intracellular signaling, calcium homeostasis, apoptosis and autophagy, which are essential for oocyte quality (48,49).…”
Section: Os-mediated Dysfunction Of Mtdna In Poimentioning
confidence: 99%